Recent advances of Copper- BTC metal-organic frameworks for efficient degradation of organic dye-polluted wastewater: Synthesis, mechanistic insights and future outlook - Roy, Saptarshi; Darabdhara, Jnyanashree; Ahmaruzzaman, Md (Journal of hazardous materials letters, 2024)
Water borne emerging pollutants represents a significant challenge confronting the modern society. As a result of excessive use of dyes and pigments by the textile and other industries, substantial amount of these toxic and recalcitrant substances are widely dispersed into the aquatic sources that may raise serious health issues to all life forms besides causing potential disruption to the ecosystem. Treatments of these hazardous and non-biodegradable organic contaminants in wastewater effluents have become a focal point for researchers dedicated to environmental remediation. Notably, Metal organic frameworks (MOFs) and their composites have been reported to be promising materials for tackling such challenges. This review is dedicated to provide a concise overview by consolidating the diverse beneficial attributes of Cu-BTC MOF rendering it as a versatile material with applications spanning diverse domains, focusing on the reactivity, the role of the metal ion and its recent potential for addressing the elimination of toxic textile dye wastes from the wastewater effluent. Furthermore, it also documents the underlying mechanistic pathway governing the degradation mechanism and the superior electron transport property of Cu ̶ BTC, besides painting in detail the existing limitations that hinder their applicability at an industrial platform. Moreover, a set of future research outlooks serving as a roadmap for exploring the potentiality of Cu ̶ BTC MOFs have also been presented. [Display omitted] •Structure and properties of Cu−BTC MOF.•Recent advancements of HKUST-1 MOF composites in remediation of dye contaminated wastewater.•Detailed explanation of the mechanism involved in photocatalysis.•Underlying present challenges and the prospect of future outlook in developing Cu−BTC photocatalysts.•Next generation smart technology for treatment of wastewater.